Aerodynamic analysis of airfoils using XFLR5: An educational approach for aerodesign competitions - Guimarães, Guilherme Henrique Moura; Silveira, Arthur Inácio Santos; Mariano, Felipe Pamplona (Brazilian Journal of Production Engineering, 2025)
Optimizing aerodynamic performance is essential for competitions such as SAE AeroDesign, and the XFLR5 software is therefore an ideal low-cost and versatile tool for this purpose. This study aims to demonstrate in a practical way the possibilities of studying and analyzing aerodynamic airfoils using XLFR5, aimed primarily at students and aeronautical engineering enthusiasts. Firstly, the functions present in XFLR5 were explained in detail, with procedures for importing, analyzing and understanding the results. Next, the flight parameters were defined, such as the Reynolds number and Mach number, as well as the choice of the aerodynamic profiles analyzed: CH10SM and S1210. The characteristics of these profiles were studied using lift, drag, momentum and efficiency graphs in XFLR5. The results indicated that the CH10SM profile has greater efficiency and lower drag, while the S1210 profile has greater longitudinal stability. In conclusion, XFLR5 has proved to be a very useful and efficient tool for learning aerodynamic concepts, and is highly relevant to model airplane projects in educational competitions such as SAE Brasil AeroDesign.